EVALUASI PENERIMAAN KINERJA HUMAN RESOURCE INFORMATION SYSTEM UNIVERSITAS BINA DARMA - Diana, Diana; Kurniawan, Kurniawan (JURNAL ILMIAH MATRIK, 2014)
This study aims to study on user acceptance levels of the Human Resources Information System (HRIS) UBD. Evaluation to see how far the system is functioning properly in accordance with its function so that the system supports the task effectively. This evaluation provides information on the perception of users that can be entered for UBD in developing HRIS in the future. The model used is Human - Organization - Technology (HOT) Fit Model. The components include human (system use and user satisfaction), organization (structure and environment), technology (system quality, information quality and service quality). Instrument research using questionnaires, scoring by using a Likert scala. Retrieved fact that, variable human, organization and technology, and a significant positive effect on the acceptance of the performance of HRIS UBD. Factors affecting the successive visits of the loading factor is variable technology (0.541 (0.001)), human variables (0.308 (0.001)), and the organization variable (0.220 (0.027)).